The bauls of Bengal : Narayan Chandra Adhikary - Music of the heart - Silvestri, Pietro (2006)
[Dt.:] Diese Webseite bietet eine kleine Einführung in die Geschichte und Musik der bengalischen Bauls, die oft als mystischer Wanderbarden umschrieben werden. Neben zahlreichen Abbildungen vor allem des Bauls Narayan Chandra Adhikary, der im Zentrum dieser Webseite steht, sind auch einige Lieder zu hören. . - [Engl.:] This website provides a short introduction into the history and the music of the Bauls of Bengal, who are often described as mystic wandering minstrels. Apart from some small articles it contains a collection of photographs (mostly of the Baul Narayan Chandra Adhikary, on whom the website focuses) and some of his songs